IMG-14. Cognitive deficits and altered functional network organization in pediatric brain tumor patients. (3rd June 2022) - Seitzman, Benjamin; Anandarajah, Hari; McMichael, Alana; Dworetsky, Ally; Coalson, Rebecca; Dowling, Anna; Mitchell, Timothy; Olufawo, Michael; Agamah, Alikem; Butler, Rachel; Jiang, Catherine; Gu, Hongjie; et al.
Abstract: INTRODUCTION: Survivors of pediatric brain tumors experience significant cognitive deficits from their diagnosis and treatment. Mechanisms of cognitive injury are poorly understood, and predictors of long-term outcome are lacking. Large-scale, distributed brain systems provide a window into brain organization and function that may yield insight into these mechanisms and outcomes. Recent evidence suggests that systems-level changes are related to cognitive performance across the lifespan. Here, we evaluated brain network architecture, cognitive performance, and brain-behavior relationships in pediatric brain tumor patients. METHODS: Forty-nine patients (ages 7-18y.o.) with any brain tumor diagnosis underwent resting state functional Magnetic Resonance Imaging (rsfMRI) during regularly scheduled clinical visits. All patients were tested with the NIH Toolbox Cognition Battery. One-hundred thirty-nine age- and sex-matched typically developing children were used as controls. All data were processed to minimize artifactual sources of variance. Functional brain networks were created for each patient via rsfMRI data from 300 regions of interest that sample the whole brain. Multilinear models were implemented to examine brain-behavior relationships, while accounting for demographic and clinical factors. RESULTS: Functional network organization was significantly altered in patients compared to controls ( p <0.001). Network organization was more affected in patients who received whole-brain radiation therapy than those who did not ( t =2.52, p <0.015). Patients demonstrated significant impairments in multiple domains of cognitive performance, e.g. attention ( p <0.0001). Weak relationships were found between cognitive performance and network organization, none of which survived multiple comparison correction. CONCLUSIONS: Brain network architecture is significantly altered in pediatric brain tumor patients. Whole-brain radiation was related to the largest changes. Most network and cognitive changes were significant with large effect sizes, yet brain-behavior relationships were weak. Our results suggest that systems-level changes in brain organization may provide insight into long-term changes in brain function in pediatric brain tumor patients.